PENERAPAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) PADA MESIN CNC TURNING MORI SEIKI SL-25 - Fahira Tamimy; Fajar Aswin; Husman (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The Bangka Belitung State Manufacturing Polytechnic has machine tools such as conventional machines in the form of lathes, milling, scrap, drills and also automatic machines such as CNC lathes, milling. The machining process used in the production process is a machining process that must comply with the demands of the production quality of CNC Turning Machines at the Polman Babel Mechanical Engineering Laboratory, which often experience damage and disrupt the performance of the machine. The purpose of this research is to identify failure modes, causes of damage, and efforts to minimize and prevent damage that can be done to improve the performance of CNC machines at the Polman Babel Mechanical Engineering Laboratory. The method used to identify and analyze possible damage to the machine uses the Filure Mode and Effect Analysis (FMEA) method and is used to find the priority of the problem through the Risk Priority Number (RPN). The results of this study indicate that there is damage to the components in the form of damage to the oil seal, damage to the en-coder, blown fuse and damage to the front door switch. The results of the analysis show that the highest RPN value is the most risky cause of failure and the main cause of damage. Proposed corrective action is to immediately replace components that are no longer functioning properly by optimizing component maintenance according to applicable instructions and rules.